Avaliação da resposta funcional e motora ao tratamento de pulsoterapia em portadores de mielopatia por HTLV-1 - SOUSA, Rayssa Alessandra Godinho de (2021)
It is estimated that approximately 15 to 20 million people are infected with HTLV worldwide. HTLV-1/2 infection is endemic in Brazil, with a prevalence of 5% of the population. There is a high incidence in Maranhão, where ten out of every 1000 blood donors are seropositive. Given the above, this study aimed to draw an epidemiological profile, as well as analyze and understand the functional and motor response to treatment with pulse therapy in patients with HTLV-1 with myelopathy. The sample consisted of 32 patients followed at the HTLV outpatient clinic of the Getúlio Vargas Hospital Unit of the State of Maranhão, who had a diagnosis of HTLV myelopathy and underwent pulse therapy from November 2018 to April 2020. Data from the medical records were used. of the patients to trace the epidemiological profile and were applied, in three moments of the treatment, as the Lawton and Brody, Katz scales and the Holden classification. Most patients were female (69%); age group 60 to 69 years (53.1%); with parity in relation to the marital status of married and widowed (37.5%) and (31.3%), respectively; from the interior of the state (59.4%), where (40.6%) had an income of less than 1 minimum wage, (37.5%) between 1 and 2 salaries and (21.9%) above 2 salaries Compatible. It is observed that (90.6%) had impairment of motor strength (56.3%) alteration in gait alteration (56.3%). With regard to walking autonomy, most were selected as independent walking (53.1%). According to the Lawton and Brody scale, none of the patients met the classification of total dependence during the trials. Around 87.5% of patients in the first assessment (month 1) were classified as having partial dependence for the development of their activities of daily living, in the second (month 3) and third (month 7) assessment it was observed that 90, 8% of the number of patients had partial dependence. For patients classified as 12.5% independent in the first assessment (month 1), there is a reduction after 6.3% of patients in the second assessment (month 3). Using a scale by Lawton and Brody, it is noted that among the patients followed, none fit the classification of total dependence to perform daily activities in the three evaluations of the study. It was observed that there was no statistical difference in the degree of dependence for performing daily activities during the study period, despite the patients reporting improvement in performing their usual activities.